2021
DOI: 10.1002/wcc.713
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of heat stress on animal cognition: Implications for adaptation to a changing climate

Abstract: With global surface air temperature rising rapidly, extensive research effort has been dedicated to assessing the consequences of this change for wildlife. While impacts on the phenology, distribution, and demography of wild animal populations are well documented, the impact of increasing temperature on cognition in these populations has received relatively little attention. Cognition encompasses the mental mechanisms that allow individuals to process information from the surrounding environment, respond accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 286 publications
(351 reference statements)
1
32
0
Order By: Relevance
“…Indeed, at 32°C, bumblebees did not extend their proboscis significantly more to the CS+ than to the CS− or the neutral mechanosensory stimulus, suggesting that all memory of the positive reward was lost. Our findings are consistent with studies in humans, mice, goldfish, nematodes and fruit flies, which also indicate that heat‐stress impairs learning and memory (reviewed in Soravia et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Indeed, at 32°C, bumblebees did not extend their proboscis significantly more to the CS+ than to the CS− or the neutral mechanosensory stimulus, suggesting that all memory of the positive reward was lost. Our findings are consistent with studies in humans, mice, goldfish, nematodes and fruit flies, which also indicate that heat‐stress impairs learning and memory (reviewed in Soravia et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…While the impact of global warming on animals is becoming the focus of an increasing body of research, very little is known about how temperature affects cognition, particularly in invertebrates (Soravia et al, 2021). Here, we provide the first evidence that elevated ambient temperatures severely impact the learning and memory abilities of an important insect pollinator group, bumblebees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat stress occurs at the temperature at which an animal cannot dissipate its entire body temperature to the surrounding environment (Sejian et al, 2018). It has been reported that heat stress plays a negative role in animal welfare and animal production, especially in broilers (Soravia et al, 2021). During heat stress, energy metabolism is reduced, leading to poor organ development and decreased mass gain (Fausnacht et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which thermal stress affects neural development and cognitive processes, such as learning in animals, are still not well understood (Buchanan et al 2013 ). Its effect is nevertheless important regardless of the mechanism and there is still little known about how thermal stress affects animal cognition (Soravia et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%